Polyhydroxyalkyl derivatives and polyetherols obtained from azacyclic compounds. Part I. Reactions with oxiranes - Lubczak, J. (Polimery, 2011)
The methods to synthesize polyhydroxyalkyl derivatives of azacycles and polyetherols with azacycles in reactions with oxiranes have been reviewed. These compounds are useful substrates for obtaining polymers of enhanced thermal stability like polyurethanes, polyesters or polyacrylates. The synthesis conditions, catalysts and solvents used for successful synthesis protocols for the substrates and chosen applications of substrates were presented.